2014
DOI: 10.1183/09031936.00212813
|View full text |Cite
|
Sign up to set email alerts
|

Medical nanoparticles for next generation drug delivery to the lungs

Abstract: Respiratory diseases are an increasing burden for the ageing population. Although our understanding of these diseases has improved significantly over the past decades, diagnostic and therapeutic options for treating lung diseases, such as chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis and lung cancer, remain limited. Multidisciplinary approaches that bridge the gap between medicinal and materials sciences will likely contribute to promising new therapeutic and diagnostic solutions. One su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 84 publications
2
84
0
Order By: Relevance
“…15,16 Surface of NDDS may be modified with antibodies, tumor markers, fluorescent dyes, magnetic materials, carbohydrates, or mucoadhesive materials. 17 It was reported that surface coating of NDDS with mucoadhesive could provide additional advantages to NDDS such as protection against degradation, 18 localization of drug at the absorption window, 19 and sustaining drug effect. 20 Chitosan (CS) is a well-known cationic biodegradable polymer that was reported to enhance small intestine permeability.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Surface of NDDS may be modified with antibodies, tumor markers, fluorescent dyes, magnetic materials, carbohydrates, or mucoadhesive materials. 17 It was reported that surface coating of NDDS with mucoadhesive could provide additional advantages to NDDS such as protection against degradation, 18 localization of drug at the absorption window, 19 and sustaining drug effect. 20 Chitosan (CS) is a well-known cationic biodegradable polymer that was reported to enhance small intestine permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The first three Back to Basics reviews covered subjects as diverse as EGFR signalling [6], medical nanoparticles [7] and the latest advances in our knowledge of CFTR dysfunction [8]. This is an exciting new feature, and we look forward to watching it develop.…”
mentioning
confidence: 99%
“…[23] The lung is considered to be a particularly well-suited organ for local drug delivery as nanoparticles can be delivered via the trachea to the respiratory epithelium of the lung where they are efficiently taken up due to its large surface area, thin epithelium layer, and rich blood supply. [24] Therefore, we next evaluated intratracheal delivery of passively and actively targeted MSNs into the lungs using the previously reported Kras LA2 mutant mouse model for lung cancer. [25] This model displays clinically relevant cancer development compared to tumor cell injection models as tumors develop spontaneously and are heterogeneously distributed ( Figure 5A).…”
Section: Alveolar Macrophages Engulf Intratracheally Administered Msnmentioning
confidence: 99%